Ice‐melt rates by steam condensation during explosive subglacial eruptions. Issue 2 (11th February 2015) - Woodcock, D. C.; Gilbert, J. S.; Lane, S. J.
Abstract: Subglacial volcanism melts cavities in the overlying ice. These cavities may be flooded with meltwater or they may be fully or partially drained. We quantify, for the first time, heat transfer rates by condensation of steam on the walls and roof of a fully or partially drained subglacial eruption cavity. Our calculations indicate that heat fluxes of up to 1 MW m −2 may be obtained when the bulk vapor in the cavity is in free convection. This is considerably smaller than heat fluxes inferred from ice penetration rates in recent subglacial eruptions. Forcing of the convection by momentum transfer from an eruption jet may allow heat fluxes of up to 2 MW m −2, consistent with values inferred for the Gjálp 1996 subglacial eruption. Vapor‐dominated cavities in which vapor‐liquid equilibrium is maintained have thermal dynamic responses that are an order of magnitude faster than the equivalent flooded cavities. Key Points: A model for free convection steam condensation heat transfer is developed Heat transfer rates may be further increased by forced convection Heat fluxes approach those inferred from recent volcanic eruptions